2013
DOI: 10.2478/chilat-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Levonorgestrel-Releassing Intrauterine System (Lng Ius) on Metabolic Markers in Women with Normal Body Mass and Overweight Women

Abstract: 27Summary Introduction. In Latvia, the number of overweight women is increasing, while the rate of cardio vascular disease (CVD) is one of the highest in the European Union. The influence of hormonal contraception on the development of CVD has not been studied in Latvia so far. Aim of the study. A nonrandomized open-label prospective trial of healthy reproductive-age women desiring to use the LNG IUS. Materials and methods. Before starting the use of contraception and six months after starting the use of contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…Similar data was observed by Vasaraudze et al (11) where they found that the LNG-IUS has no significant adverse effects on any of these parameters, which could further lead to risk of any of the metabolic disorders. In contrast, Bender et al (12) determined an increase in body weight and abdominal circumference.…”
Section: Discussionsupporting
confidence: 88%
“…Similar data was observed by Vasaraudze et al (11) where they found that the LNG-IUS has no significant adverse effects on any of these parameters, which could further lead to risk of any of the metabolic disorders. In contrast, Bender et al (12) determined an increase in body weight and abdominal circumference.…”
Section: Discussionsupporting
confidence: 88%
“…A longer follow-up with large number of subjects will only lead to know the effect of LNG-IUS on lipid profile. Similar data was observed by Vasaraudze I et al 9 In a randomized comparative study among Asian population, LNG-IUS does not have any adverse effects on lipid metabolism. 10 In present study, in anthropometric data, significant reduction from baseline was seen in case of both BMI and waist circumference at 6 months.…”
Section: Discussionsupporting
confidence: 88%
“…8 In the present study, SBP was 120.38±5.62mmHg, DBP 74.57±4.59mmHg, and mean fasting blood glucose 86.37±6.61mg/dL. Vasaraudze 9 The occurrence of high BP during use of an LNG-IUS has been studied several times, but none of the studies, with a follow-up of 1-10 years could find a relation. 2 Total cholesterol increased at 6 months; HDL and VLDL increased at 6 and 9 months.…”
Section: Discussionmentioning
confidence: 51%